2007
DOI: 10.1590/s1516-14392007000300002
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of thermoplastic starch/zein blends

Abstract: Blends of starch and zein plasticized with glycerol were prepared by melting processing in an intensive batch mixer connected to a torque rheometer at 160 °C. The resulting mixtures were compression molded and then characterized by scanning electron microscopy, differential scanning calorimetry, wide-angle X ray diffraction and water-absorption experiments. The blends were immiscible, showing two distinct phases of starch and zein. The water uptake at equilibrium and its diffusion coefficient were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 12 publications
6
52
1
6
Order By: Relevance
“…In the Figure 4b it is possible to verify the spectra of the films and the corn starch. In corn starch there is a band at 2933 cm -1 representing the methyl group of the CH stretching, a spectrum at 1087 cm -1 related to the stretching of secondary and primary alcohols and another spectrum at 1648 cm -1 related to the presence of water 6 . In all spectra of biofilms a band between 3000 and 3500 cm -1 related to the stretching of OH bond was observed.…”
Section: Abstract: Starch Plasticizer Properties Carboxylic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Figure 4b it is possible to verify the spectra of the films and the corn starch. In corn starch there is a band at 2933 cm -1 representing the methyl group of the CH stretching, a spectrum at 1087 cm -1 related to the stretching of secondary and primary alcohols and another spectrum at 1648 cm -1 related to the presence of water 6 . In all spectra of biofilms a band between 3000 and 3500 cm -1 related to the stretching of OH bond was observed.…”
Section: Abstract: Starch Plasticizer Properties Carboxylic Acidsmentioning
confidence: 99%
“…This starch characteristic has attracted a strong interest in conventional polymer market by incorporating it in polymer mixtures 2 . In addition, the use of starch is an excellent alternative for edible films and coatings due to its easy processing, low cost, abundance, biodegradability and edibility [3][4][5][6][7] . The plasticizers are generally, small and low volatile molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The consistency index (K-value), an indication of shear viscosity (Xie et al, 2009) was also substantially reduced when zein was blended with pregelatinized maize starch compared to the pre-gelatinized maize starch (Table 2). Similarly, Corradini et al (2007) reported a reduction of starch melt viscosity when blended with zein. The apparent viscosity and K-value of the blends decreased with decreasing the proportion of the starch from 3 Starch: 1 zein to 1 starch: 1 zein and 1 starch: 3 zein.…”
Section: Resultsmentioning
confidence: 86%
“…However, the blending of starch and zein to produce a stable co-polymer is a challenge due to the relative hydrophobic nature of zein owing to its high contents of non-polar amino acids (Tihminlioglu et al, 2011) and the hydrophilic nature of starch. Corradini et al (2007) and Habeych et al (2008) have reported starch-zein incompatibility based on morphological and microscopic evidence, which displayed two separate phases of starch and zein during hot melt blending. To overcome this, Leroy et al (2012) used an ionic liquid [(1-butyl-3-methylimidazolium chloride [BMIM](Cl)] to produce a starch-zein thermoplastic blend by melt processing using a twin screw micro-compounder.…”
Section: Introductionmentioning
confidence: 99%
“…Muitos polímeros biodegradáveis provenientes da biomassa vêm sendo estudados, especialmente os polímeros naturais baseados em precursores polissacarídicos [1] , tais como a celulose e seus derivados [2] , a quitina e quitosana [3] , e o amido termoplástico [4,5] . Este último, também conhecido na literatura como TPS, tem destaque por sua facilidade de processamento em condições típicas de polímeros em geral, permitindo a produção de filmes, injetados e expandidos [6] . No entanto, apesar destes materiais permitirem o descarte direto, a sua origem natural muitas vezes dificulta a padronização de propriedades como resistência mecânica e permeabilidade a gases, sendo freqüentes os problemas relacionados à reprodutibilidade.…”
Section: Introductionunclassified